Property Management Excellence : A Values-Based Approach to Real Estate and Property Investing. - Luna, Anthony A.; ProQuest (firma) (Newburyport : Advantage Media Group, 2025)
In Property Management Excellence, Anthony A. Luna shares his journey from growing up in the Harbor Area of Los Angeles to becoming CEO of Coastline Equity in his thirties. More than a guide to managing real estate, this book is a blueprint for building a business rooted in integrity and values-driven management.
Description based on publisher supplied metadata and other sources.
Part of the metadata in this record was created by AI, based on the text of the resource.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2026. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Leadership; Real estate management; elektronické knihy; electronic books